2016
DOI: 10.1016/j.molmet.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The satiating hormone amylin enhances neurogenesis in the area postrema of adult rats

Abstract: ObjectiveAdult neurogenesis in the subgranular zone and subventricular zone is generally accepted, but its existence in other brain areas is still controversial. Circumventricular organs, such as the area postrema (AP) have recently been described as potential neurogenic niches in the adult brain. The AP is the major site of action of the satiating hormone amylin. Amylin has been shown to promote the formation of neuronal projections originating from the AP in neonatal rodents but the role of amylin in adult n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
1
16
1
Order By: Relevance
“…Clinical and animal studies have recently looked at the unique relationship between amylin and cognition. 88 , 89 Similar to the finding by Qiu, 90 the concentration of amylin was markedly decreased in the DC rats. It is worth mentioning that amylin hormone potently enhances the translocation of Aβ peptide from the brain into blood.…”
Section: Discussionsupporting
confidence: 77%
“…Clinical and animal studies have recently looked at the unique relationship between amylin and cognition. 88 , 89 Similar to the finding by Qiu, 90 the concentration of amylin was markedly decreased in the DC rats. It is worth mentioning that amylin hormone potently enhances the translocation of Aβ peptide from the brain into blood.…”
Section: Discussionsupporting
confidence: 77%
“…As the primary site of IAPP action, the area postrema (AP) is the brain structure best characterized in terms of IAPP effects. While IAPP was shown to promote the formation of AP neuronal projections in neonatal rodents, in adult Wistar rats, IAPP injections were reported (1) to affect genes controlling neurogenesis, particularly NeuroD1, (2) to increase the number of newly proliferated AP-cells, and (3) to promote differentiation of these cells into neurons (Liberini et al, 2016). A study to investigate the mechanism by which IAPP modulates neuronal excitability in AP neurons in rat brainstem slices revealed that IAPP induced changes in excitatory responses of neurons not displaying the hyperpolarization-activated cation current.…”
Section: Iapp Pathology In the Brainmentioning
confidence: 99%
“…The male mice were removed thereafter. Dams were injected twice 12 h apart with BrdU at E12 (75 mg/kg sc, Sigma Aldrich, Buchs, Switzerland) (22,23,30). The day of the birth was designated as P0.…”
Section: Brdu Injection and Genotypingmentioning
confidence: 99%
“…The role of amylin as a neurogenic factor has been recently examined in adult rats; exogenous amylin, which was continuously infused in male adult rats for 4 wk, increased cell birth and favored neurogenesis in the AP (30). However, the neurogenic role of amylin during embryogenesis has never been assessed.…”
Section: Introductionmentioning
confidence: 99%